2016
DOI: 10.1093/heapro/daw083
|View full text |Cite
|
Sign up to set email alerts
|

How do brochures encourage walking in natural environments in the UK? A content analysis

Abstract: Although walking for leisure can support health, there has been little systematic attempt to consider how recreational walking is best promoted. In the UK, local authorities create promotional materials for walking networks, but little is known about whether they effectively encourage walking through persuasive messaging. Many of these materials pertain to walks in natural environments which evidence suggests are generally visited less frequently by physically inactive individuals. Consequently the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Outcome expectancy messages were subsequently classified as targeting affective, instrumental, or both affective and instrumental attitudes. The work of Elliott et al (2016) guided how we formatted our codebook. As Gainforth et al (2011) did not present operational definitions to the informational sources of self‐efficacy (e.g., mastery experiences), we adapted definitions provided by Mead et al (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome expectancy messages were subsequently classified as targeting affective, instrumental, or both affective and instrumental attitudes. The work of Elliott et al (2016) guided how we formatted our codebook. As Gainforth et al (2011) did not present operational definitions to the informational sources of self‐efficacy (e.g., mastery experiences), we adapted definitions provided by Mead et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…There appear to have been at least three applications of the CAATSPEC in the physical activity domain (Elliott et al, 2016; Gainforth et al, 2011, Tristani et al, 2017), two of which focused on print materials. Elliott et al (2016) analyzed brochures advertising recreational walking paths, Gainforth et al (2011) analyzed physical activity promotion brochures primarily intended for nonclinical adults and disseminated through medical and health care offices, and Tristani et al (2017) analyzed educational websites intended for parents of children with disabilities. These studies provide some insight as to the precise integration of theory‐based and empirically supported behavioral change concepts, principles, and techniques within educational materials for lay adults.…”
Section: Introductionmentioning
confidence: 99%
“…A two-page extract from an existing recreational walking brochure from Devon, UK ( Elliott et al , 2016 ) was used as the ‘original brochure’ condition ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, even policy-level approaches acknowledge the necessity of understanding individual cognitions and actions when developing community-wide approaches to physical activity promotion. Despite this recommendation though, a content analysis of behaviour change messages in recreational walking brochures produced by such authorities in the UK concluded that their text frequently does not target theory-based behaviour change mechanisms known to influence physical activity uptake ( Elliott et al , 2016 ) and thus may not promote recreational walking optimally for less active adults. Although brochures or leaflets, even if effectively optimized, do not represent a solution on their own, they are a commonly used way to communicate the appeal of an area and walking opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…The main strength of this study is the development and testing of a novel methodology for enhancing confidence that BCTs present in behavioral intervention descriptions are operationalized in intervention materials as intended. An independent coder was used with no involvement in the development of eMotion who was experienced in coding behavior change materials (Elliott et al, 2018). This reduces the possible bias of finding BCTs due to previous knowledge of the intervention development process.…”
Section: Strengths and Limitationsmentioning
confidence: 99%